Nociceptor Neurons Magnify Host Responses to Aggravate Periodontitis. (July 2022) - Wang, S.; Nie, X.; Siddiqui, Y.; Wang, X.; Arora, V.; Fan, X.; Thumbigere-Math, V.; Chung, M.K.
Periodontitis is a highly prevalent chronic inflammatory disease that progressively destroys the structures supporting teeth, leading to tooth loss. Periodontal tissue is innervated by abundant pain-sensing primary afferents expressing neuropeptides and transient receptor potential vanilloid 1 (TRPV1). However, the roles of nociceptive nerves in periodontitis and bone destruction are controversial. The placement of ligature around the maxillary second molar or the oral inoculation of pathogenic bacteria induced alveolar bone destruction in mice. Chemical ablation of nociceptive neurons in the trigeminal ganglia achieved by intraganglionic injection of resiniferatoxin decreased bone loss in mouse models of experimental periodontitis. Consistently, ablation of nociceptive neurons decreased the number of osteoclasts in alveolar bone under periodontitis. The roles of nociceptors were also determined by the functional inhibition of TRPV1-expressing trigeminal afferents using an inhibitory designer receptor exclusively activated by designer drugs (DREADD) receptor. Noninvasive chemogenetic functional silencing of TRPV1-expressing trigeminal afferents not only decreased induction but also reduced the progression of bone loss in periodontitis. The infiltration of leukocytes and neutrophils to the periodontium increased at the site of ligature, which was accompanied by increased amount of proinflammatory cytokines, such as receptor activator of nuclear factor κΒ ligand, tumor necrosis factor, and interleukin 1β. The extents of increase in immune cell infiltration and cytokines were significantly lower in mice with nociceptor ablation. In contrast, the ablation of nociceptors did not alter the periodontal microbiome under the conditions of control and periodontitis. Altogether, these results indicate that TRPV1-expressing afferents increase bone destruction in periodontitis by promoting hyperactive host responses in the periodontium. We suggest that specific targeting of neuroimmune and neuroskeletal regulation can offer promising therapeutic targets for periodontitis supplementing conventional treatments.